2017
DOI: 10.1039/c7ra01160a
|View full text |Cite
|
Sign up to set email alerts
|

Can sodium silicates affect collagen structure during tanning? Insights from small angle X-ray scattering (SAXS) studies

Abstract: The effect of sodium silicates on collagen structure during leather processing was investigated. Small angle X-ray scattering (SAXS) and differential scanning calorimetry (DSC) reveal that the molecular structure and thermal stabilities of the sodium silicate treated leathers (So-Si and So-Si + BCS) were different to the conventionally processed chromium treated leathers (BCS). The collagen fibrils were observed to be coated by aggregates of silica, which did not affect the axial periodicity (D-period) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
1
23
0
2
Order By: Relevance
“…In recent years, Zhang et al . revealed that the electrostatic interactions between silicate species and amino groups in collagen molecules can promote formation of silica aggregates coating on the surface of collagen fibers, while there was virtually no improvement on the stability of collagen . Surprisingly, in our recent work, we found that the shrinking temperature, thermal denaturation temperature and porous structure of the leather was improved obviously, by using the silicic acid derived from sodium silicate in the tanning process .…”
Section: Introductionmentioning
confidence: 67%
“…In recent years, Zhang et al . revealed that the electrostatic interactions between silicate species and amino groups in collagen molecules can promote formation of silica aggregates coating on the surface of collagen fibers, while there was virtually no improvement on the stability of collagen . Surprisingly, in our recent work, we found that the shrinking temperature, thermal denaturation temperature and porous structure of the leather was improved obviously, by using the silicic acid derived from sodium silicate in the tanning process .…”
Section: Introductionmentioning
confidence: 67%
“…However, chrome tanning causes a decrease in the quantity of all three natural crosslinks. During chrome tanning, the carboxylate (−COO − ) groups of aspartic (Asp) and glutamic (Glu) acid residues of collagen are bonded covalently [7], causing significant structural changes in collagen [40,41]. Similarly, the removal of structure stabilizing natural crosslinks can also cause changes in the collagen structure [3,42].…”
Section: Quantification Of Natural Crosslinks In Skin Collagen: Relatmentioning
confidence: 99%
“…Collagen molecules are aligned in a quarter stagger structure, resulting in repeating gap/overlap regions within the fibrils [12,13]. Because of its ordered arrangement, molecular level information can be acquired by Xray scattering techniques, including diffraction, to measure the periodicity of the gap/overlap regions (D-period) and the size of collagen fibrils [14][15][16][17][18][19]. The interactions between water and collagen play a crucial role in the stability of the triple helix [20][21][22].…”
Section: Introductionmentioning
confidence: 99%